THE RELATIONSHIPS BETWEEN ISLAM AND LOCAL CULTURE - Rohmah, Khayatur (UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This article is the result of a research that did with the purpose to know the process of Islam Relation and local culture. The research is a study about sea alms tradition and also the religion values of Kertojayan village, Grabag district, Purworejo regency. The methoad of the research used qualitative approach with descriptive type. The subject is society of Kertojayan village. The result shows that; (1) Islam Relation process and local culture in sea alms ceremony tradition of Kertojayan village have brought by a missionary (Kiai) who involved in sea alms ceremony tradition and he got a support from regent of Purworejo. Some of peoples accept the tradition and they are moslem. (2) The religion values that consist in sea alms tradition of Kertojayan village have three three values, there are loyalty symbol and thank feel to Allah, religion values like recited the prays and attitude value such as cooperate to keep a clean area.